Rediscovering the Geographic Space through the Geographical Space - Delfina Trinca Fighera (GEOUSP: Espaço e Tempo, 1998)
This paper purposes to discuss the technical matter as an essential expression of the relationship between the Man and the nature. So, it approachs a geographical view of the human action over the nature, trying to understand the construction of "today"' and its configuration on our time